The Motif of the She-Wolf in the Foundation Myths of Rome and the First Turkic Khaganate - Szewczyk, Rafał; Kowalska, Martyna (Vade Nobiscum, tom XXV/2025: Varia, 2025)
The article is a characterization and comparison of two foundation myths – Rome and the First Turkic Khaganate – with an indication of the similarities and differences in both stories. The content related to the founding myths has been supplemented with a historical or historical-mythical outline, as well as the most important information regarding the sources dealing with the issues discussed in the article. The work focuses primarily on the motif of the wolf appearing in stories about many societies throughout history. The she-wolf is one of the most important, central characters of the founding myths analyzed in the article, although her presence in each of them can be explained by the desire to emphasize other phenomena and values.